DINAMIKA INFEKSI Balantidium coli DAN Strongyloides sp. PADA ORANGUTAN (Pongo pygmaeus) CAPTIVE DAN SEMI-CAPTIVE DI TAMAN NASIONAL TANJUNG PUTING KALIMANTAN TENGAH - , SUPRIADI, Dr. Drh. R. Wisnu Nurcahyo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Balantidium coli and Strongyloides sp. infection is well-known to have impacts on the health of captive and semi-captive orangutans. The aim of this research is to study the infection proportion and mean infection intensity differences of B. coli and Stongyloides sp. in captive and semi-captive orangutans based on age and sex group, in addition to the infection association between the two parasites in orangutans from the Tanjung Puting National Park, Central Kalimantan. The samples were examined in laboratory by employing saturated sugar flotation method. Next, the samples which show positive infection of B. coli and Strongyloides sp. were analyzed utilizing McMaster method to count the number of eggs, larvae, cysts and/or trophozoids. The results showed there was no significant difference of B. coli infection (Ï 2 = 0,518